Shariah Governance: Perspective of Islamic Finance - Miajee, Md. Rezaul Karim (International Journal of Shari’ah and Corporate Governance Research, 2018)
The present short paper is an attempt to anlyze the Shariah Governance of Islamic Finance. Corporate governance issues are especially important in developing economies, since these countries do not have a strong, long-established financial institution infrastructure to deal with corporate governance issues.